2022
DOI: 10.3389/fnut.2022.832341
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dietary Protein Intake and Sleep Quality in Middle-Aged and Older Adults in Singapore

Abstract: Poor sleep has been associated with the increased risk of developing detrimental health conditions. Diet and certain nutrients, such as dietary protein (PRO) may improve sleep. This cross-sectional study aimed to investigate the relationship between PRO intake, their amino acid components, and sources with sleep quality in middle-aged and older adults residing in Singapore. A dataset of 104 healthy subjects between the age of 50 and 75 years old were used. Collected data included 3-day food record and sleep qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…16 Sutanto and colleagues showed that dietary tryptophan has a significant positive correlation with sleep duration. 31 However, they reported that that there is no clear correlation between high-protein diets and sleep quality and latency. Halson and colleagues state that increasing carbohydrate intake can decrease sleep latency and increasing protein intake can increase sleep quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Sutanto and colleagues showed that dietary tryptophan has a significant positive correlation with sleep duration. 31 However, they reported that that there is no clear correlation between high-protein diets and sleep quality and latency. Halson and colleagues state that increasing carbohydrate intake can decrease sleep latency and increasing protein intake can increase sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that high‐protein diets enhance sleep quality indices, 22,29,30 although some studies do not report an explicit relationship between high protein intake and sleep quality 16 . Sutanto and colleagues showed that dietary tryptophan has a significant positive correlation with sleep duration 31 . However, they reported that that there is no clear correlation between high‐protein diets and sleep quality and latency.…”
Section: Discussionmentioning
confidence: 99%
“…As already discussed, Trp is an essential amino acid that, after passing the brain blood barrier, is converted in serotonin and ultimately to melatonin, which promotes sleep. Sleep duration is positively associated with the dietary Trp: LNAA ratio ( 37 ). The reason for which this ratio among dietary intake of Trp and LNAA is related to sleep duration may be due to the fact that LNAA compete with Trp to bind to a carrier protein to pass the blood–brain barrier ( 157 ), influencing brain Trp bioavailability.…”
Section: Clinical Evidence In Humansmentioning
confidence: 99%
“…The authors observed that sleep duration was directly related to the protein intake ( 140 ). A study in 104 healthy adults and older individuals from Singapore investigated the relationship among protein intake and sleep, focusing on tryptophan intake ( 37 ). Sleep duration was positively associated to dietary Trp: LNAA ratio but also to plant Trp and plant Trp: LNAA, and this interestingly suggest that the source of protein may play a role.…”
Section: Clinical Evidence In Humansmentioning
confidence: 99%
See 1 more Smart Citation